The structure and content of locally-produced children’s television programmes in Nigeria (2012)
This study examined the structure and content of locally-produced children’s television programmes with a view to finding out the quality and appropriateness of the media content that children are exposed to in Nigeria. It also investigated the factors affecting the quality of locally produced television programmes targeted at the child audience. Data were obtained through content analysis and in-depth interviews. Three locally produced children’s programmes (‘Children’s Funtime’ – BCOS-TV, 'Children’s Funspace’ – Galaxy TV, ‘Kids and Food’ – NTA Network all in Ibadan, Nigeria) were selected for the study. Eighteen episodes of the selected programmes were content analyzed while twelve purposively selected broadcasters were interviewed. Findings showed that though the entertainment-education content of the programmes were geared towards meeting the socialisation needs of the child audience, some programmes lacked professional packaging as evident in poor post-production such as missing inter-segmental links, substitution of closing montages with captions as well as poor and unstable timing. Factors which determine the quality of media content revealed in the study include media funding, competence of producers and level of participation of children. The study, therefore, recommended adequate funding of children’s television productions as well as training and re-training of broadcasters to ensure quality programmes production.